Adolescent education: an opportunity to create a Developmental Origins of Health and Disease (DOHaD) circuit breaker. (7th July 2016) - Bay, J. L.; Vickers, M. H.
Abstract : Health before conception, and periconceptional nutritional environments, contribute to conditioning of later-life health and disease. Health behaviors developed during adolescence continue into adulthood. Thus, even when the gap between pregnancy and adolescence is substantial, behaviors developed during adolescence influence later-life non-communicable disease (NCD) vulnerability in offspring. Consequently, adolescence is an important life phase where development of positive health behaviors can contribute to disruption of transgenerational cycles of NCD risk. Schooling is a core activity during adolescence. Modern curricula focus on development of capabilities associated with critical, engaged citizenship, empowering learning that supports action-based engagement in complex issues. Contexts relevant to adolescents and their communities, such as the NCD epidemic, are used to facilitate learning. Thus, engaging the education sector as participants in the work of the Developmental Origins of Health and Disease community offers an important strategy to capture the potential of adolescence as a life stage for transgenerational primary prevention of obesity and NCD risk.